Multi-band perfect absorption induced by breaking the symmetry of metamaterial structure - Tiep, Dinh Hong; Tung, Bui Son; Khuyen, Bui Xuan; Lam, Vu Dinh (Vietnam Journal of Science and Technology, 2019)
In this work, a multi-band metamaterial perfect absorber is demonstrated numerically and experimentally in the microwave region based on the breaking symmetry of geometrical structure. Initially, when the structure, which is designed in the X shape, is in the symmetric geometry, only one absorption peak is observed. By breaking the symmetry of structure, new absorption peaks emerge, leading to the multi-band perfect absorption. In addition, the separations of absorption peaks are proportional to the degree of geometrical asymmetry. Our work presents a simple and efficient approach to create multi-band metamaterial perfect absorbers.